Decision Making Behavior of Individual Stock Investors’ in Nepal - Basnet Chhetri, Raju (Journal of Nepalese Business Studies, 2022)
The study’s primary objective is to explore the factors influencing the individual investors’ decision making behavior of Nepalese stock investors and to examine the relative degree of influence of such factors with respect to various demographic and socio-economic characteristics. The study follows quantitative approach and exploratory and descriptive research designs. Survey was conducted during March through May, 2021 obtaining 505 usable responses. Factor analysis was performed to explore the influential factors. The factor “Accounting and stock market information” was revealed to be of highest influence in decision making behavior of individual stock investors. The effect of “Public and economic information” was found to be significantly different between male and female investors; surprisingly not among different age groups. “Accounting and stock market information” was found to be significantly different among investors with various educational qualifications. Classical rational criteria such as expected dividends, expected corporate earnings, dividends paid and condition of financial statements were found to be most influential variables. While most respondents seemed to be unaware of the consequences of the contemporary issues like environmental record, increase of firm’s involvement in solving community problems and perceived ethics of firm, the need for relevant awareness and educational campaigns regarding the importance of social, ethical, environmental value of investments seems alarming.